PERSEPSI MAHASISWA PGSD TERHADAP BAHAN AJAR E-LEARNING MATA KULIAH MEDIA PEMBELAJARAN - Kristi Wardani; Ayu Rahayu; Akbar Al Masjid (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to develop teaching materials and to know the perception of PGSD students on teaching materials e-learning courses of instructional media. The research method used is survey method with previously conducted research development method. The population in the study were PGSD UST students who took the Learning Media course in the Even Semester of the academic year 2016/2017 with samples taken by cluster random sampling (random sampling by class). Data collection techniques were done by distributing questionnaires to respondents. Data analysis is done descriptively with table frequency distribution. The results showed that the perception of PGSD students on learning materials e-learning subjects of SD Learning Media included in either category. This is shown in the results of research stating that 81% of the respondents have a good perception.